The Characteristics Of Kidney Stone Patients And Their Management At Dr. Pirngadi Medan General Hospital In 2016 - Soufi Amira; Siti Kemala Sari (Publikasi Indonesia, 2024)
Kidney stones are formation of new crystals of urine solution in the urinary tract due to changes in the saturation of substances in the urine. Incidence of lidney stones increased over three decades The prevalence of kidney stones occurs in 0.3% of cases in North Sumatra. From the results of a preliminary survey at RSUD Dr. Pirngadi Medan in 2016, the number of kidney stone patients was 81 people. This is a descriptive study using a retrospective case study design to determine the characteristics of kidney stone patients and their management at Dr. Pirngadi Medan General Hospital in 2016. Data were taken from medical record of patients woth kidney stones diagnosed in Agustus - September 2017 and analyyzed and presented in tables. we found that the incidence of kidney stones was higher in male (56,2%) than in female (43%)., with the highest incidence in the 46-52 year age group (26,25%) and the lowest in the >70 age group, and the majority of patients had no history family with kidney stones (83.8%). Based on education, the highest proportion of patients is at senior high school (78,8%) and the lowest proportion at the college level (5%). Highest incidence found in enterpreneur (32,5%) followed ny housewives (30%) and driver was the lowest (1,2%). Management of kidney stones chategorized by medication in 16 people (20%), and surgery in 64 people (80%) The highest characteristics based on educational background were the group with Senior High School graduates, and the majority of sufferers had self-employed jobs.. Complete data regarding kidney stone cases is needed for future larger descriptive epidemiological studies